Representasi Maskulinitas Tokoh Utama dalam Film Persahabatan Bagai Kepompong 2021 - Annisa Fitria Ramadhani; Catur Suratnoaji (Jurnal Nomosleca, 2021)
The research aims to illustrate and understand the meaning of the representation of masculinity of the main character in the film "Friendship Like a Cocoon" directed by Sentot Sahid. This research is qualitative research using primary and secondary data collection techniques obtained from reference books, scientific journals, and articles. The study used an analysis of Roland Barthes' Semiotics data that had three levels of tagging: denotation, connotation, and myth that focused on seven characteristics of masculinity expressed by Janet Saltzman Chafetz, namely: 1) Male Physical Appearance, 2) Male Functional, 3) Male Sexual, 4) Male Emotions, 5) Male Intellectuals, 6) Male Interpersonal, and 7) Male Personal Character.Keywords: Film, Janet Saltzman Chafetz's Concept of Masculinity, Semiotics Roland Barthes.